IMPLEMENTASI PEMURIDAN DEEPER 3.0 UNTUK MENINGKATKAN KEDEWASAAN ROHANI PENGERJA GEREJA DI GEREJA BETHEL INDONESIA TABGHA BATAM - Robertus Suryady (JURNAL TABGHA, 2023)
Spiritual maturity is the task of the church in cultivating the congregation according to what is written in Ephesians 4:13 until we have all achieved unity of faith and true knowledge of the Son of God, full maturity, and a level of growth that corresponds to the fullness of Christ. It is the responsibility of all parties to increase this spiritual maturity. Various methods are used to achieve this goal. One of them is discipleship which is included in the Deeper 3.0 module. This article uses a qualitative method with a literature study approach and theological journals for writing. Meanwhile, the implementation uses sustainable discipleship techniques. The results found that through the implementation of the Deeper 3.0 discipleship module for the Gereja Bethel Indonesia Tabgha Batam workers, they provided successful results in their efforts to spiritually mature the congregation.